Improving the effectiveness of self education of future teachers of technology - O. G. Fedorenko (Academy of Cognitive and Natural Sciences, 2015)
Using cloud technology in the educational activities require adjustment not only form but also teaching methods, and therefore the question of expediency implementation of cloud technologies for self education. Constructed methods and recommendations allow the use of cloud technology as a part of information and educational environment and meet the challenges of the primitive educational products, performance and objectivity purpose of education, choice of individual educational trajectory and reflection.